RELATIONSHIP BETWEEN MISCONCEPTION AND MATHEMATICAL ABSTRACTION OF GEOMETRY AT JUNIOR HIGH SCHOOL - Gida Kadarisma; Nelly Fitriani; Risma Amelia (Jurnal Infinity, 2020)
This study aims to examine the misconceptions that often occur in junior high school students on the concept of geometry based on abstraction level. The research method is qualitative with a case study design. Subjects in this study are 27 students of the 3rd grade of junior high school students, who had to learn all the concepts that will be appeared on the test. Material that will be given on the test of this research is the concept of Triangle, Quadrilateral, Flat Side Geometry and Curved Side Geometry. This research takes a place at one of the junior high schools in Cimahi. The instrument in this study is a diagnostic test (to find out the types of students’ misconception), mathematical abstraction tests (to determine the level of abstraction) and interview rubrics. Misconceptions produced by students are closely related to students’ mathematical abstractions, the higher the level of abstraction ability, the more students away from misconceptions. The topic taken in this study is the topic of basic geometry, the results can be a source of information about the types of misconception that often occur in students, and how the solution so that these misconception do not re-occur.